Effect Of Explosive Strength Training On Middle-distance Performance Of Junior Male Runners. - Abdennouz, Hamza; Chaichi, Kheireddine; Azzizi, Brahim; Nasri, Djamel; Belaid, Akil Abdelkader (جامعة الوادي - University of Eloued, 2022)
The present study was conducted to illustrate - through a training program (based on simultaneous Strength / Endurance training) - the importance of strength in improving performance in middle distance. We used the experimental method that contains two groups, experimental group and control group; the athletes of both groups will perform the following tests: ¼ squat test at 110°, 20m launched sprint and 3000m running. The two groups will follow a training for 6 weeks (2 hours / session, 5 sessions / week), 25% and less than 5% of the training time were devoted to the explosive force training respectively for the experimental and the control group. We will do a re-test afterwards to see the evolution of performance in both groups.
article
Keywords: Explosive Force, Sports performance, Middle distance races